Saneamento de Pelotas (1871-1915): o patrimônio sob o signo de modernidade e progresso - Xavier, Janaina Silva (2010)
This dissertation presents the results of a research work developed in the Master's degree in Social Memory and Cultural Patrimony of the Federal University of Pelotas. The study analyzes the first initiatives of sanitation of the city of Pelotas (RS) started through the installation of a private dealership called Hydraulic Company from Pelotas that in 1871, implanted the services of water supply. Later, the municipal public power created the Section of Waters and Sewers, through which annulled the Hydraulic Company in order to enlarge the services of water and to build the first sewers system that it was inaugurated in 1915. The work presents the sanitary situation of Pelotas before the services of water and sewers, the reasons that took the city to look for the sanitary improvements, where the public administration found references, the path of the works, the results and the repercussion close to the local society. The dissertation still discusses the modernity concepts and progress present in Europe in the XIX century and its influence in the urbanization of the cities and does a brief analysis of the historical and cultural patrimony of the sanitation of Pelotas